2017
DOI: 10.1007/s10840-017-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T elevation after permanent pacemaker implantation

Abstract: Pacemaker implantation was found to be accompanied with CTNT elevation in 55.6% of the patients at 6 h after the procedure, and its kinetics were fast, which might not be related to the complications and adverse cardiac outcomes within 1 year of follow-up. Moreover, gender, NT-pro-BNP at baseline, LVEF, eGFR, and fluoroscopy time were found to be independent predictors of CTNT elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, the mild and transient elevation of cTNT in our study did not contribute to the poor prognosis, indicating that the increase in cTNT is mostly transient myocardial injury caused by occluder implantation, which does not affect cardiac ejection function and ventricular survival area. Our results were consistent with previous studies (28,29). Similarly, all patients in our study were followed up for 1 year, and the cTNT elevation had no relation to the complications of the procedure or cardiac outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…However, the mild and transient elevation of cTNT in our study did not contribute to the poor prognosis, indicating that the increase in cTNT is mostly transient myocardial injury caused by occluder implantation, which does not affect cardiac ejection function and ventricular survival area. Our results were consistent with previous studies (28,29). Similarly, all patients in our study were followed up for 1 year, and the cTNT elevation had no relation to the complications of the procedure or cardiac outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…By retrieving related reports, we compared the troponin T change between RVP in a previous study 4 and LBBAP in this study. As shown in table 4, the myocardial damage of LBBAP was more serious than that of We explored the overall population to identify variables correlated with the increase of troponin T. Linear regression analysis was used to adjust for covariates that were found in the correlation analysis.…”
Section: Comparison With Other Types Of Ventricular Pacingmentioning
confidence: 99%
“…It is reported that transvenous insertion of the leads is followed by a sequence of cardiac histopathological changes, leading eventually to the formation of a fibrous connective tissue scar 3 . In the traditional way of pacing, most patients have a very slight troponin elevation after pacemaker implantation, leading to consider that it is not harmful to cardiac function and structure 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not identify any relation of increased biomarkers with procedure-related complications, lead displacement or rise in pacing threshold during a 1-month follow-up period. Consequently, this elevation in plasma cardiac biomarkers most likely represents the minimal myocardial damage that occurs during device implantation and seems not to be of clinical importance [13,14] .…”
Section: Discussionmentioning
confidence: 99%